Mechanistic study of vitamin C attenuation of endometriotic fibrosis - X.J. Shi; L.B. Shi; S.Y. Zhang (Clinical and Experimental Obstetrics & Gynecology)
Background: Endometriosis is a common disease in females that seriously affects quality of life. The principal pathological process of endometriosis is pelvic inflammation, and local and peripheral fibrosis. Treatment of endometriosis requires both pharmacological and surgical approaches. Vitamin C can scavenge oxygen free radicals and thus accelerate repair of damaged endometrium. This aim of this study was to investigate whether vitamin C can reduce fibrosis in endometriotic lesions. Methods: After establishing a rat model of endometriosis, vitamin C solution (vitamin C group) or physiological saline solution (control group) was injected into the abdominal cavity. We compared the indices of fibrotic endometriotic lesions between the two groups. Results: The volume of endometriotic lesions and degree of fibrosis observed in rats within the vitamin C group was significantly reduced compared with those observed in the control group. Immunohistochemistry showed that transforming growth factor-β1 (TGF-β1), connective tissue growth factor (CTGF), α-SMA, and collagen type I staining in lesions of the vitamin C group was significantly less than that observed in lesions from the control group (P < 0.05). Quantitative, real-time PCR (RT-PCR) determined that relative mRNA expression levels of TGF-β1, CTGF, α-SMA, and collagen type I in lesions obtained from the vitamin C group were significantly lower than levels measured in lesions obtained from animals in the control group. Conclusion: Vitamin C can reduce the volume of endometriotic lesions and inhibit fibrosis of lesions in rats. This study supports the use of vitamin C in the treatment of endometriosis.